Factors associated with HPV awareness among mothers of low-income ethnic minority adolescent girls in Los Angeles. Issue 2 (3rd January 2015) - Glenn, Beth A.; Tsui, Jennifer; Singhal, Rita; Sanchez, Leah; Nonzee, Narissa J.; Chang, L. Cindy; Taylor, Victoria M.; Bastani, Roshan
Abstract Among caregivers of adolescent girls, awareness of human papillomavirus (HPV) is strongly associated with vaccine uptake. Little is known, however, about the predictors of HPV awareness among low-income ethnic minority groups in the U.S. The purpose of this study is to understand demographic factors associated with HPV awareness among low-income, ethnic minority mothers in Los Angeles County. We conducted a cross-sectional study of caregivers of adolescent girls through the Los Angeles County Department of Public Health Office of Women's Health's hotline. The majority of the participants were foreign-born (88%), one quarter lacked a usual source of care, and one quarter lacked public or private health insurance for their daughter. We found that one in three participants had never heard of HPV or the vaccine. Mothers that were unaware of HPV were significantly more likely to conduct the interview in a language other than English and to lack health insurance for their daughters. HPV vaccine awareness was much lower in our caregiver sample (61%) than in a simultaneous national survey of caregivers (85%). The associations between lack of awareness and use of a language other than English, as well as lack of health insurance for their daughter indicate the need for HPV vaccine outreach efforts tailored to ethnic minority communities in the U.S.